2019
DOI: 10.1111/gcb.14550
|View full text |Cite
|
Sign up to set email alerts
|

Examining forest resilience to changing fire frequency in a fire‐prone region of boreal forest

Abstract: Future changes in climate are widely anticipated to increase fire frequency, particularly in boreal forests where extreme warming is expected to occur. Feedbacks between vegetation and fire may modify the direct effects of warming on fire activity and shape ecological responses to changing fire frequency. We investigate these interactions using extensive field data from the Boreal Shield of Saskatchewan, Canada, a region where >40% of the forest has burned in the past 30 years. We use geospatial and field data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 75 publications
5
84
0
Order By: Relevance
“…Short interval fires can have an outsized impact on ecosystem functioning due to a lack of adaptation to the increased fire frequency (Walker et al 2018), sometimes resulting in forest loss (Jackson et al 2009). As a result, the impacts of reburning over relatively brief intervals are a major research focus (Buma et al 2013, Hart et al 2019, Stevens-Rumann and Morgan 2019, Turner et al 2019. Rapid, directional ecosystem changes, such as converting those forests to alternate ecological regimes (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short interval fires can have an outsized impact on ecosystem functioning due to a lack of adaptation to the increased fire frequency (Walker et al 2018), sometimes resulting in forest loss (Jackson et al 2009). As a result, the impacts of reburning over relatively brief intervals are a major research focus (Buma et al 2013, Hart et al 2019, Stevens-Rumann and Morgan 2019, Turner et al 2019. Rapid, directional ecosystem changes, such as converting those forests to alternate ecological regimes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…But for how long?It is vital that we understand the prevalence, trends, and correlating factors with reburning in recently burned forest ecosystems, but while there are many excellent local and landscape scale investigations of reburning trends and feedback mechanisms (e.g. Parks et al 2016, Harvey et al 2016, Erni et al 2017, Tepley et al 2018, Hart et al 2019, a broad-scale assessment of trends has not been attempted. It is important to determine if trends and feedbacks suggested at finer scales do indeed scale up to broad regional patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The observed state shifts were largely attributed to the effect of fire on species regeneration (e.g. seedbanks) 36,37 . Fire and climate change, in concert, can affect tree regeneration further south as well, in P. ponderosa and P. menziesii forests, with warmer temperatures unsuitable for conifer seedlings that emerged after fire 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies found that Great Xing'an boreal forests will experience severe fire activities that were characterized as more frequent and large burns with higher severity along with climatic changes and fuel accumulation [18,85,86]. It is not difficult to speculate that coniferous forests may experience more recovery limitations, which has been validated in boreal forests of Central Siberian [84] and North America [8,11]. Besides, very high severity fires may have also killed broadleaf tree species and understory species whose roots would otherwise provide a source of asexual reproduction even if above-ground portions are killed, creating opportunities for primary succession.…”
Section: The Response Of Forest Recovery To Spatial Controlsmentioning
confidence: 93%
“…In general, forest ecosystems are resilient and able to recover key functional and compositional attributes after disturbances [6][7][8]. However, the resilience of boreal forests is decreasing due to a misalignment between changing fire regimes and vulnerable ecosystem states [9][10][11]. Biome transitions in boreal forests, including shifts from forests to treeless steppes and an increase in deciduous trees, are thought to be exacerbated by changing fire regimes [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%